AI and creativity: Effects of culture and task emotiveness in human-AI collaboration - TAN, Choon Ngee (Institutional Knowledge at Singapore Management University, 2024)
Creativity is the driving force behind innovation, propelling individuals and societies toward progress by generating novel ideas and groundbreaking solutions. The emergence of generative AI models, exemplified by GPT-3, offers opportunities to enhance human creativity. This paper explores the potential for unprecedented breakthroughs through the synergy between human intuition and AI-driven creativity, providing practical guidance on leveraging AI to amplify creative capacities. Study 1 finds that AI models trained on data from the U.S. and Chinese cultures exhibit cultural norms, values and cognition of those cultures. Study 2 finds that when humans and AI models of the same culture collaborate on local tasks, humans experience greater flow, leading to better creative usefulness. However, these effects do not occur for global tasks. Study 3 finds that AI models alone perform better on cognitive rational tasks than on emotive tasks, especially for creativity usefulness. Humans outperform AI models on creativity, especially for creativity usefulness. When humans and AI models collaborate, the creative outcomes are superior to humans working alone or AI models working alone. In such collaborations, the human contribution of emotional empathy enhances the emotional depth and beauty of the results. Study 4 conducted in the field corroborates the findings of Studies 2 and 3.